PENGARUH STRES KERJA TERHADAP PENINGKATAN TEKANAN DARAH PADA PEKERJA - Indah Kurniasari; Sho'im Hidayat (Universitas Airlangga, 2017)
Work stress occurs when the demands of the job do not match with capabilities, resources, needs and worker discontent. One of the effects of work stress is increased blood pressure. This study was performed to determine the effect of work stress on the increased of blood pressure in press cutting PT.X. This study is analytical study which is explain the influence work stress to increase of blood pressure. This study using cross sectional methodology. The population of this study is people who work at press cutting PT. X who ammount to 40 persons. The sampling technique is total sampling. In order to knowing the influence of work stress to increase of blood pressure that is using logistic regression and then that is explanning at naration and tables. The result of this study show that from 40 respondent 35.00 % getting work stress. Respondent who get work stress and increased the blood preasure is 25.00 % from 40 respondent. And also that is showing mean of blood pressure and increase blood pressure respondent’s who get work stres higher than respondent who do not get work stress. Using logistic regression obtain Exp(B)= 5.625. It is showing at worker who get work stress have risk of increase blood pressure higher than do not get work stress. Keyword: increase of blood pressure, press cutting workers, workstress